Michael Mann cinema and television : interviews, 1980-2012 (Edinburgh University Press, 2014)
This reader is the first to bring together a selection of Mann's own interviews where he reflects on his film and television productions. The sixteen interviews provide historical context, interpretation and evaluation of the auteur's work. They encompass his entire career as a feature filmmaker and television producer/director as he and others reflect on his themes, working methods, artistic development and career achievements. The book aims to open up Mann's body of work, making it available for comparison with the work of his contemporaries, and to provide fresh insights into his film and television work. A substantive introductory essay, chronology and filmography provide additional bases for understanding the interviews, essays and work of this major filmmaker.Key Features* The first reader on Michael Mann *Includes three interviews originally published in French periodicals and translated for this volume *Open up Mann's body of work, making it available for comparison with the work of his contemporaries